Does market react to tax reduction news? An empirical study on corporate tax reduction of Bangladesh in 2017-18 - Adnan, ATM (Business, Management and Economics Engineering, 2019)
Purpose – This study tries to investigate the capital market reaction to the corporate tax reduction announcement (37.5% from 40%) in Bangladesh for publicly listed Banking, Insurance and Financial Institutions of 2017-18. Methodology – This study applied an event study approach to identify any significant average abnormal returns as well as cumulative average abnormal returns of all the publicly listed Banks, Insurances and Financial institutions around the announcement period. Findings – Insignificant average abnormal return (AAR) experienced in case of Banking and Insurance industry on event day, except the financial institutions which have generated a statistically significant abnormal negative return on announcement day. The combined AAR of all three sectors has also generated statistically insignificant return around event windows which suggest that investors did not consider tax reduction news as valuable information for investment decision nor considering it as an essential factor of share value. Limitation – The study did not consider any possible extraneous variable that could result in insignificant reactions. Practical Implication – The findings of this research would considerably contribute to the financial and economic policy formulation while taken into consideration the possible impact of the policy over the capital market of Bangladesh. Originality – This study makes a considerable input to the research in the area of taxes linked to the behavioural finance applying the unique variable of investor’s reactions.